2019
DOI: 10.1039/c9cy01298b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the oxygen coordination environment of Ca–Mn oxides on the catalytic performance of Pd supported catalysts for aerobic oxidation of 5-hydroxymethyl-2-furfural

Abstract: Pd/CaMn2O4 provides ideal active sites for oxygen adsorption and desorption, resulting in the promoted charge transfer ability and catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…2(a) further demonstrates that the choices preference of soluble bases in the HMF oxidation reactions listed in Tables 1-3 were closely correlated with reaction time and temperature, although determined primarily by the activity of catalysts. The structural parameters of catalysts like particle size, exposed crystal planes, and metal-support interaction have obvious effects on the reaction turnover frequency [25][26][27][28][29][30][31][32]. Siyo et al [25] reported that the Pd nanoparticles (NPs) with a mean diameter of 1.8 nm in an alkaline aqueous solution (T = 90°C, p O2 = 0.1 MPa) afforded up to 90% yield of FDCA.…”
Section: Single Noble Metal Catalystsmentioning
confidence: 99%
“…2(a) further demonstrates that the choices preference of soluble bases in the HMF oxidation reactions listed in Tables 1-3 were closely correlated with reaction time and temperature, although determined primarily by the activity of catalysts. The structural parameters of catalysts like particle size, exposed crystal planes, and metal-support interaction have obvious effects on the reaction turnover frequency [25][26][27][28][29][30][31][32]. Siyo et al [25] reported that the Pd nanoparticles (NPs) with a mean diameter of 1.8 nm in an alkaline aqueous solution (T = 90°C, p O2 = 0.1 MPa) afforded up to 90% yield of FDCA.…”
Section: Single Noble Metal Catalystsmentioning
confidence: 99%
“…[91b] The bimetallic catalysts containing precious metal and transition metal were also applied for aerobic oxidation of HMF. Four types of CaÀ Mn oxides, CaMnO 3 , CaMn 2 O 4 , CaMn 3 O 6 , and Ca 2 Mn 3 O 8 , have been prepared by Liu and co-workers [94] and used as supports for Pd nanoparticles for catalytic oxidation HMF. Pd/CaMn 2 O 4 exhibits promoted oxygen activation capacity and stronger electron transfer ability and thus the highest catalytic activity among these catalysts.…”
Section: Production Of Fdcamentioning
confidence: 99%
“…Co p )/N-CNTs] was also prepared from ZnCo-ZIF and applied for HMF oxidation, and the synthesis process was shown in Figure 17. Outstanding catalytic performance was exhibited due to the preferable catalytic activities of Co single atoms (Co 1 ) and Co nanoparticles (Co p ), and the catalyst achieved 100 % HMF conversion efficiency and 96 % FDCA yield under 0.1 MPa O 2 atmosphere at 100 °C for 8 h. [101] Manganese oxides have been extensively investigated in broad fields, such as use as catalysts [99,102] or the supports of active metal, [94,95] owing to their low cost, Earth abundance, and specific chemical properties. It is generally acknowledged that manganese oxides have diverse crystal structures and a redox cycle between + 2 and + 4 oxidation states, providing outstanding redox reactions of Mn 2 + /Mn 3 + or Mn 3 + /Mn 4 + , and oxygen mobility within the oxide lattice.…”
Section: Production Of Fdcamentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] White et al later characterised the magnetic behaviour of the material as antiferromagnetic from SQUID magnetometry. 20 As with delafossite materials, Ca 2 Mn 3 O 8 has been investigated for the catalytic splitting of water [21][22][23][24][25][26][27] and as a potential battery electrode. 28 However, the understanding of the structure-property relationships in Ca 2 Mn 3 O 8 has largely been limited by the low crystallinity of the as synthesised materials.…”
Section: Introductionmentioning
confidence: 99%